Learning about learning: developing conservatoire students’ pedagogical knowledge - Luan Shaw (Journal of Learning Development in Higher Education)
Conservatoires are specialist and practical schools that provide immersive training for aspiring performing arts professionals. Historically, performance training in music has been valued over and above other aspects of the curriculum in conservatoires. For example, learning how to teach is rarely considered as important as learning how to perform. Yet pedagogical training in music has enormous potential to support students to learn about their own learning development and that of others, and as such can enhance students’ employability in or beyond music. Whilst this article focuses on the discipline of music, it poses important questions about the value for students of learning about learning via pedagogical training in many other creative subject areas, such as dance, drama, art, and languages, or even STEM subjects (sciences, technology, engineering, and mathematics). Developing students’ metacognitive awareness may benefit society, helping students to nurture the next generation of learners, whilst impacting positively on longer-term recruitment into conservatoires and other Higher Education Institutions.